Add fish to your dish - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Integrated agriculture aquaculture. A primer FAO, 2001. 151 pp. ISBN 92 5 104599 2 US$ 20 Euro 22.70